Cryptic diversity of the semi-terrestrial amphipod Platorchestia japonica (Tattersall, 1922) (Amphipoda: Talitrida: Talitridae) in Japan and Taiwan, with description of a new species - Cheng, Yu-Ting; Nakazono, Kenji; Lin, Y. Kirk; Chan, Benny K. K. (Zootaxa, 2011)
The talitrid amphipod Platorchestia Bousfield, 1982 is common in sandy beaches, estuarine marshes, shores of lakes and rivers. They are detritivores, and being prey for birds and other animals, they play an important role in the food chain. In the present study, we identified a new Platorchestia from Guan-du, Taiwan, based on morphological (light microscopy and scanning electron microscopy) and molecular approach (sequence divergence in the mitochondria DNA, COI) and described herein. Platorchestia paludosus sp. nov. from the Guan-du was morphologically different from all reported Platorchestia species, but it was very close to P. japonica (Tattersall, 1922). The distribution pattern of setae in the lateral margin of the telson and sharpness of ramus tip of uropod 3, however, exhibit diagnostic differences between the two species. From sequence divergence in COI, Platorchestia paludosus differed from P. japonica 13.3% in average, values that are comparable to inter-specific differences in other amphipod taxa.